Comparison Of ALT In Type 2 Diabetics with And Without Fatty Liver Disease - Malik, Kausar; Batool, Faiza; Meraj, Lubna; Saddiq, Shazia; Akbar, Abrar; Mughal, Hina Hanif (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the association of alanine aminotransferase in type 2 diabetic patients with and without fatty liver disease. Materials and Methods: A cross-sectional study was done for six months at Sheikh Khalifa Bin Zaid Al-Nahyan Hospital Rawalakot. In our study, we included all the patients who presented to the outpatient department (OPD) having type 2 diabetes mellitus. Their age, gender, height, weight, and duration of diabetes mellitus were noted. Their liver function test (LFTS), fasting blood sugar and HBA1c, and fasting lipid profile were also done at the time of their OPD visit and results were noted. They were given an appointment for an ultrasound abdomen from the radiology department for detection of fatty liver disease and the results were noted on the next OPD visit. Results: Total study population was 90 patients and out of which 35 (38.8%) were male and 55 (61.1%) were female. 58 years was the mean age of our study population. Fatty liver was present in 50% of patients. ALT was raised from a baseline value of 36 in 61% of patients while fasting blood sugar was raised in 83% of patients. The mean fasting blood sugar was 208 mg/dl. ALT was not significantly different in patients with and without fatty liver disease. However, it was found that patients with uncontrolled blood glucose levels have significantly raised ALT which was also statistically proven as the P value was less than 0.05. Also, patients with high blood glucose have a higher incidence of fatty liver disease as compared with normal blood glucose level patients but the difference was not statistically significant as shown by a P value more than 0.05. Conclusion: Fatty liver disease is more common in Type 2 diabetic patients with uncontrolled blood sugar. There is a high rate of raised ALT in diabetic patients whose blood sugar control is not optimum.